Through Women’s Eyes. Conference Interpreters’ Self-Perceived Status in a Gendered Perspective - Gentile, Paola (HERMES - Journal of Language and Communication in Business, 2018)
This paper aims to analyse the differences between female and male conference interpreters’ self-perceived status. Several studies (Angelelli 2004; Katan 2011; Zwischenberger 2011) indicate that women make up most of the professionals working in the translational professions, but little academic attention has been devoted to the question as to whether female and male interpreters have different attitudes towards their profession and their self-perceived status. Sociological studies on feminised professions suggest that women are generally underestimated in the workplace, which leads to them to perceive their status as lower compared to their male colleagues (Cortina/San Román 2006). To test whether this phenomenon was experienced by conference interpreters as well, the responses of a world survey (n = 805) were analysed, with a special focus on interpreters’ self-perception of the status, prestige and social value of their profession. The results showed that, when asked to evaluate their self-perceived status, there were hardly any differences between the scores obtained by female and male interpreters. However, major differences emerged when men and women expressed their opinions on the way they think their work is seen by laypeople, showing that female interpreters perceive their status as far lower than their male counterparts do.